Size Selective Synthesis of Superparamagnetic Nanoparticles in Thin Fluids under Continuous Flow Conditions - Chin, Suk Fun; K., Swaminathan Iyer; Raston, Colin L.; Saunders, Martin (WILEY-VCH Verlag GmbH & Co., 2008)
Continuous flow spinning disc processing (SDP), which has extremely rapid mixing under plug flow conditions, effective heat and mass transfer, allowing high throughput with low wastage solvent efficiency, is effective in gaining access to superparamagnetic Fe3O4 nanoparticles at room temperature. These are formed by passing ammonia gas over a thin aqueous film of Fe2þ/3þ which is introduced through a jet feed close to the centre of a rapidly rotating disc (500 to 2500 rpm), the particle size being controlled with a narrow size distribution over the range 5 nm to 10 nm, and the material having very high saturation magnetizations, in the range 68–78 emu g-1.